Implementasi Model Pembelajaran Kooperatif TGT Melalui Pendekatan Taktis Keterampilan Bermain Bola Voli Mini dan Kepercayaan Diri Siswa Sekolah Dasar - Aulia Rahma; Agus Mahendra; Eva Sri Gumilang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of implementing the cooperative learning model Teams Games Tournament (TGT) through a tactical approach on mini volleyball playing skills and self-confidence of elementary school students. This research used a quantitative approach with a quasi-experimental method and a nonequivalent group pretest-posttest design, involving 40 fifth-grade students of SDN 062 Ciujung divided into an experimental group and a control group through purposive sampling technique; data were collected using the Game Performance Assessment Instrument (GPAI) and a self-confidence questionnaire, then analyzed using the Wilcoxon Signed Rank Test, Mann-Whitney U Test, and Paired Samples T-Test. The results showed that (1) the TGT model through a tactical approach had a significant effect on improving mini volleyball playing skills (Sig. = 0.000); (2) the model had a significant effect on students' self-confidence (Sig. = 0.000); so it can be concluded that this learning model is effective to be applied as an alternative learning strategy for Physical Education, Sport, and Health in elementary schools. Keywords: Elementary School, Mini Volleyball, Self-Confidence, Tactical Approach, TGT Model